Evaluation of the Efficiency of 2 Types of Periodontal Probing - Martu Alexandra; Popa C.; Luchian I.A.; Martu Ioana; Oanta Cornelia; Martu Silvia (Balkan Journal of Dental Medicine, 2015)
Background: The periodontal probing has an important role in clinical examination of the periodontal status; different types of periodontal probes have been described. The aim of this investigation was to evaluate comparatively the efficiency of periodontal probing with conventional periodontal probe and electronic periodontal probe.